The Role of Psychological Factors in Visha w.s.r to Poison - Rajendra , H M; Karikatti, Deepa; Swathi, M (International Research Journal of Ayurveda & Yoga, 2022)
Psychological factors play a very important role in visha. The definition of visha itself gives the term depression. When the person is affected by visha, there are not only symptoms of body but mind is also involved. There are references of shanka visha, sarpangaabhihata etc. where mind is involved. From a psychiatric standpoint, exposure to toxins can increase the risk of depression, suicide, ADD/ADHD, learning problems, memory problems and dementia, brain fog, autism, temper outbursts, and psychotic behavior. Over the last four decades, there has been the unprecedented development and release of a swelling repertoire of potentially toxic chemicals which have the capability to inflict brain compromise. The treatment of poisoned person depends on the mental status of that person, if the person is frightened, depressed the treatment given becomes of less effective. The treatment modalities of visha like mantra, Sajna Sthapana, Harshana and Santvana signifies the importance of psychological factors. This article highlights the importance of psychological factors in visha.